Rose Kretsinger (1886-1963): Renowned Quilt Artist of Emporia - Barbara Brackman (Symphony in the Flint Hills, 2012)
The history of master quiltmaker, Rose Kretsinger of Emporia.
Keywords: quilts; sewing; quilt; stich; art; botanical; folk art; tradition; Indian; Native American; Greek mythology; culture; Rose Francis Good Kretsinger; professional; School of the Art Institute of Chicago; Alphonse Mucha; Arts and Crafts; master quiltmaker; museum; Spencer Museum